Structural Evolution of Porous Carbon Materials Derived from Hemp Fibers: Raman Spectroscopy Studies - Zapukhlyak, R.I.; Kotsyubynsky, V.O.; Boychuk, V.M.; Rachiy, B.I.; Abaszade, R.G.; Hoi, V.T.; Klymyuk, M.M. (Physics and Chemistry of Solid State, 2025)
Raman spectroscopy was employed to investigate the structural evolution of porous carbon materials derived from hemp fibers through steam-assisted carbonization at temperatures of 400, 500, 600, 700, 800, and 900°C (K series), followed by nitric acid activation (KN series) and additional annealing in air (KNO series). The study is based on a comparison of the efficiency of two-component and five-component approximations for analyzing the 800-2000 cm⁻¹ spectral range in the Raman spectra of porous carbon. The two-component model, which describes only the D and G bands, provides a simplified assessment of graphitization and defect concentration, allowing for a quick evaluation of structural disorder by analyzing the ratio of the integrated intensities of the ID and IG spectral bands. The five-component approximation, incorporating the D₁, D₂, D₃, D₄, and G bands, offers a more detailed analysis of structural defects, significantly improving spectral fitting consistency (R² = 0.95-0.99) compared to the two-band model (R² = 0.80-0.88). A comparison of lateral crystallite size estimations using both approaches revealed a strong correlation between the obtained data (Pearson’s r = 0.83-0.87) across all material series, confirming the reliability of the applied analytical methods. Additionally, the five-component model identified a correlation between the D₃ band position and crystallite size, a relationship that was not evident in the two-component approximation. These findings emphasize the effectiveness of the five-component deconvolution of Raman spectra for tracking structural transformations in carbon materials, providing additional insights crucial for material selection in energy storage, catalysis, and sorption applications.